Embodying #TatakIIT: Factors influencing green purchase intention of MSU-IIT students - BANSE, JESSA MAE (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
Human activities have led to environmental problems that resulted in changes in the climate and the environment. As such, firms are starting to incorporate environment-friendly food products to help solve this issue. Consequently, the Mindanao State University-Iligan Institute of Technology (MSU-IIT) addresses the call for action by incorporating in its program curriculums the institutional outcome (#TatakIIT attributes) that relates to being environmentally responsible. Anchored on the Theory of Planned Behavior (TPB), this study investigates the influencing effects of MSU-IIT students’ awareness of environment-friendly alternatives (EFA), environmental concern, functionality of EFA, and price sensitivity to their green purchase intention (GPI), with attitude towards EFA as a mediating variable. Further, the moderating effect of the socio-demographic factors were explored. Using Partial Least Square - Structural Equations Modeling, the findings of this study suggest that all the independent variables had a significant influence on the attitude towards EFA implying a greater GPI of said alternatives. This provides evidence that when students are aware about green alternatives and have higher environmental concerns, their attitude towards green products are also intensified. However, it must be noted that the functionality of the green alternative and price still play a role which may suggest that despite being aware of EFA and environmentally concerned, the green alternatives must still be reasonably priced and serve their purpose. Attitude towards EFA successfully mediated the four independent variables and GPI, which further confirms the TPB relationships. Thus, students who have positive attitudes towards EFA are the ones who are more likely to show an intent to purchase these alternatives. However, the socio-demographic factors are deemed to have no moderation effect in the relationships between the independent variables and the attitude towards EFA, except for age. Consequently, it moderately impacts the influence of price sensitivity on the attitude towards EFA.